Meningococcal B Vaccines as a Paradigm of Safe and Effective Vaccines for Children - Maribel Gonzalez Tome; Rosa Gonzalez-Quevedo; Maria Escudeiro dos Santos; Hans Juergen Dornbusch; Sabine Straus; Emer Cooke (Vaccines)
Background: Neisseria meningitidis B is one of the main causative pathogens of meningitis and other forms of severe meningococcal disease. In the past decade, meningococcal B vaccines have been developed to address this infection and its sequelae. Objective: This article aims to present an example of how the EU regulatory framework allowed the early authorisation of two life-saving vaccines initially based on immunogenicity surrogates of clinical evidence. This was subsequently followed by post-marketing surveillance providing real-world evidence to support their safety profile and impact on the paediatric population in the EU. Methods: We review the evidence supporting the initial regulatory approval of the vaccines, the confirmatory data demonstrating vaccine effectiveness post-authorisation, and the real-world impact of these vaccines on the paediatric population. Results: Two vaccines were approved in the EU for active immunisation to prevent IMD caused by MenB (4CMenB in 2013 and MenB-fHBP in 2017). Both marketing authorisations were based on immunogenicity data (efficacy studies were not feasible due to the rarity of the disease) and safety data generated from pre-authorisation studies. Additional pharmacovigilance activities to further investigate the safety profile and effectiveness studies were requested to be conducted after approval. Both the effectiveness and safety profile of the vaccines were confirmed by these data. Conclusions: This paper illustrates that the EU medicines regulatory framework and safety monitoring system are robust. By supplementing the initial evidence with post-authorisation studies, further effectiveness and safety data enabled regulators to confirm the positive benefit–risk of the vaccines without delaying their access to the people who need them.